High-dose medium-term HMB supplementation did not trigger body composition changes in trained and untrained males under usual conditions or high-intensity functional exercise - Durkalec-Michalski, Krzysztof; Czlapka-Matyasik, Magdalena; Podgórski, Tomasz; Marchelek-Myśliwiec, Małgorzata; Nowaczyk, Paulina M. (Frontiers in Nutrition, 2025)
Introductionβ-hydroxy-β-methylbutyrate (HMB) supplementation may support fat-free mass (FFM) increase and fat mass (FM) decrease. Its utility has been studied mainly for 3 gHMB·day−1 and long-term supplementation (e.g., 12 weeks). Therefore, new and personalized effective HMB supplementation protocols should be verified.MethodsNinety trained (TR, n = 53; 29.1 ± 7.7 years; FFM: 84.1 ± 5.1%) and untrained (UTR, n = 37; 32.3 ± 7.6 years; FFM: 75.7 ± 7.7%) males completed the randomized parallel-group placebo (PLA)-controlled study aiming at evaluating the influence of new individualized high-dose mid-term liquid HMB free acid supplementation protocol (90 mgHMB·kgFFM−1·day−1) alone (3 weeks; first period) and combined with high-intensity functional training (HIFT; 3 weeks; second period) on body mass (BM), FFM and FM, and total body water (TBW). The Fight Gone Bad (FGB) workout was an additional HIFT stimuli (2 units·week−1). Testing was performed at baseline (BAS) and after the first (SUP) and the second (SUP+FGB) study periods.ResultsHMB doses were 4.8–7.8 gHMB·day−1. The intervention had no significant effect on BM, FFM, FM, or TBW. BM, FFM (kg), TBW, and TBW/FFM were higher at SUP+FGB vs. BAS regardless of the implemented treatment and training status. Nevertheless, there was an impact (p < 0.05) from training status (but not HMB/PLA) on FM (kg; slight increases in UTR) and TBW (slight decreases in UTR).DiscussionThe individually adjusted high HMB dose did not change body mass and composition in trained or untrained individuals during a three-week exclusive supplementation or three-week supplementation in combination with additional HIFT stimuli. Therefore, any modifications in this area may likely require a longer treatment period.